Benchmarking and selection of Power-to-Gas utilizing electrolytic hydrogen as an energy storage alternative. (25th May 2016) - Walker, Sean B.; Mukherjee, Ushnik; Fowler, Michael; Elkamel, Ali
Abstract: Power-to-Gas is an energy storage and transportation technology which is useful for the development of the 'smart grid', including the integration of intermittent renewable energy sources through the provision of energy storage capacity. To accomplish this, surplus or intermittent power is used to produce hydrogen via water electrolysis. As hydrogen is an energy vector, converting the power into gaseous hydrogen is considered to be an effective energy storage alternative. Previous studies attempt to qualitatively compare energy storage technologies considering criteria such as market maturity, efficiency, and cost, and include energy storage systems such as electrochemical batteries, pumped hydro or compressed air energy storage systems. In this work an Analytical Hierarchy Process is applied to compare Power-to-Gas with other energy storage technologies in applications ranging from residential load shifting to bulk energy storage and utility-scale frequency support. The authors find that Power-to-Gas is desirable in utility scale energy storage applications where criteria such as energy portability, energy density and ability for seasonal storage are considered. Highlights: Energy storage systems and applications analyzed using Analytical Hierarchical Process. Power-to-Gas concept benchmarked with other technologies. Key criteria previously unused including: transportability and seasonal storage. P2G effective, hydrogen injected in natural gas infrastructure and provides ancillaries. P2G preferred technology for distributed power generation, and energy storage.